KETIMPANGAN PEMBANGUNAN REGIONAL DAN INVESTASI DI KABUPATEN BANJARNEGARA - Wibowo, Hendri; Sasongko, Lutfi Aris (CENDEKIA EKSAKTA, 2021)
This study aims to determine the level of development inequality and investment factors that influence development inequality in Banjarnegara Regency. This research is a descriptive and quantitative research. The data used in this study are secondary data in the form of times series data, namely Gross Regional Domestic Product (GRDP), population, Foreign Investment (PMA) and Domestic Investment (PMDN) from Central Agency Statistics (BPS) of Banjarnegara Regency. The descriptive analysis technique is the Williamson Index inequality, while quantitative analysis is used to use panel data regression analysis of the Fixed Effect model. The results show the Williamson Index in 2002-2020 in Banjarnegara Regency that in 2013 it had a value of 0.580 (the highest than other years). This indicates that development inequality in Banjarnegara Regency is still occurring. The results also show that the Foreign Investment variable has no significant effect on regional development inequality with a probability of 0.964. Meanwhile the Domestic Investment variable (PMDN) has significant effect to development inequality with a probability of 0.000. Considering the policies related to investment, development should be focused on sectors that have multiplier effects for the welfare of the people in Banjarnegara Regency.Keywords: Investment Development, Data Panel, Banjarnegara Regency